The Political Thought of Jean Bodin (Journal of human and social sciences, 2015)
This paper discusses the political thought of the French thinker Jean Bodin, focusing on his theory of sovereignty and the origin of the state. It examines the influence of political and social conditions in France on his ideas and analyzes the concept of absolute sovereignty and its limitations. The study also compares different forms of government from Bodin's perspective.
Keywords: Jean Bodin; Political Thought; Sovereignty; State; Religious Wars